Malaysia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that the Malaysian economy has shown resilience and continues to perform well. Policy priorities are governance reforms and fiscal consolidation while safeguarding growth and financial stability. Structural reforms are needed to boost productivity and help further rebalancing growth towards domestic demand. Domestic demand is expected to remain the main driver of growth over the medium term. Risks to the outlook are to the downside and stem mainly from external sources. The paper also discusses that with growth returning to sustainable levels and no underlying inflation pressures, maintaining the current broadly neutral monetary policy stance is appropriate. Exchange rate flexibility should remain the first line of defence against external shocks. Also, governance reforms should be anchored in legislation to ensure the independence of anti-corruption institutions and appropriate separation of powers. Focus should be on improving the transparency and efficiency of public services.